Impact of Marine Pollution Threats and Conservation of Marine Biodiversity - Thavasimuthu Citarasu (International Journal of Marine Life, 2024)
Ocean occupies 71% of earth’s surface and is traditionally divided into four large basins including North and South Atlantic, North and South Pacific, Arctic and Indian oceans. In India we have a vast coastal area of 7516.6 km from Kolkata to Gujarat and also many islands including Andaman and Nicobar and Lakshadweep with vast fin and shellfish biodiversity. Human interference and both natural and artificial factors pose the biggest threat to the marine ecosystem. These days, various pollutants generated by human activity have a major negative impact on marine environments. The significance of the marine ecosystem, the state of the marine biodiversity, the marine protected area, the activities of natural and human-induced species that impact the biodiversity, and conservation tactics were all covered in this review. The pollutants also seriously affect the marine flora, fauna and disturb the food chains. Natural radiation, storms, waves (including cyclones), volcanic lava, tsunamis, vertical movement of ocean waters, global warming, and freshwater runoff were a few of the factors that were discussed. Discussions were also held regarding the human-related anthropogenic activities that included oil spills, hazardous heavy metals, persistent toxic substances (PTS), radiation, thermal discharges, ship-based hazards, harmful algal blooms, plastics and microplastics, ocean acidification, solid wastes, coastal tourism, ballast water, and marine littering. Ultimately, the tools, bylaws, and act were discussed in relation to biodiversity and environmental conservation. The public must strictly observe the laws governing maritime and coastal activities. The laws and acts including Indian port act 1902, Water act 1974 (prevention and control of pollution), Wildlife protection act 1972, Fisheries Management and Conservation Act – 1976, National Marine sanctuaries Act of 1972, Clean Water Act of 1977, Environment protection act 1987 and Endangered Species Act, Indian fisheries act 1987, Marine zones of India act 1987, Oceans Act of 2000 and Estuaries and Clean Waters Act of 2000 etc
Keywords: Marine Biodiversity; Marine Protective Area; Pollution; conservation